PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP DAYA BELI MASYARAKAT YOGYAKARTA DI INDOMARET - Muhammad Faiz Muzaffar; Subarjo (Jurnal Ekonomi dan Bisnis, 2026)
The competitive dynamics of modern retail in Yogyakarta marked by the dense proliferation of Indomaret outlets across residential areas, educational zones, and tourism centers present a compelling context in which the real determinants of consumer purchasing power demand empirical scrutiny. This study examines the influence of price, promotion, and product quality on the purchasing power of Yogyakarta consumers at Indomaret, both partially and simultaneously. A causal quantitative approach was employed, utilizing survey methodology as the primary data collection strategy. Through purposive sampling, 128 respondents were selected from active Indomaret consumers across the Special Region of Yogyakarta, predominantly consisting of students aged 20–30 years residing in Sleman, Bantul, and Yogyakarta City. Data were gathered via a five-point Likert scale questionnaire and subsequently analyzed using multiple linear regression through SPSS software. Partial testing revealed that price exerts a positive and significant influence on purchasing power, as does promotion. Product quality, however, proved statistically insignificant a finding that reflects the quality standardization inherent in nationally-networked minimarket chains, where perceived quality variation among consumers tends to be minimal. Simultaneous testing confirmed that all three variables collectively exert a positive and significant influence on consumer purchasing power at Indomaret in Yogyakarta.